Fungsi Pappaseng Toriolo Dalam Masyarakat Bugis Soppeng Kajian Etnolinguistik - Nurul Fitriani Fitri; Nensilianti Nensilianti; Suarni Syam Saguni (Universitas Negeri Makassar, 2021)
Abstract. This study aims to reveal the function of the pappaseng of the Soppeng community, in terms of ethnolinguistic studies. This research is descriptive qualitative. The data in this study are pappaseng . The data source in this study is the interview with the Donri-donri village community, who was interviewed in Soppeng district, 2021. The data analysis techniques are in the form of data reduction, data presentation, inference and verification. The results showed that pappaseng which was passed down to the Soppeng community, Donri-donri village, found various types of pappaseng. In pappaseng found two functions that are known and the most dominant, namely as a guide in social life and as a protector of social norms. Keywords: Culture, pappaseng, types, functions, ethnolinguistics.